Implementation of 25-well culture plates for M. tuberculosis drug susceptibility testing in Indonesia (Medical Journal of Indonesia, 2005)
At present, there is no standardized method for Mycobacterium tuberculosis drug susceptibility testing (DST) among laboratories in Indonesia. Since January 2001 to January 2004 we have tried to establish the method of 25-well culture plates with middlebrook's media (Drug Susceptibility Culture Plate (DSCP) method) used by the Dutch Supranational Reference Laboratory at the Institute of Public Health and the Environment (RIVM), Bilthoven, Netherlands. Our experience showed that this method potentially gives better result as it can be very well standardized, faster and provides detailed MIC (Minimal Inhibitory Concentration) values. Data from 364 isolates that have been tested by DSCP method showed that resistance to INH, rifampicin, ethambutol, and streptomycin were 21.4%, 19.8%, 15.7%, and 16.5% respectively. Multidrug resistance were found in 13.2% isolates. (Med J Indones 2005; 14: 142-6)